TELAAH HUKUM ISLAM TERHADAP FENOMENA SILARIANG SEBAGAI JALAN PINTAS PERKAWINAN DI MASYARAKAT BUGIS SULAWESI SELATAN - Alamsyah, Tahwin; Kurniati, Kurniati; Misbahuddin, Misbahuddin (Law Journal (LAJOUR), 2025)
The phenomenon of silariang in the Bugis community of South Sulawesi presents a complex socio-cultural issue that persists over time. Silariang refers to couples marrying without parental approval, considered a grave violation of family honor (siri’). This practice arises from various factors such as social status differences, economic pressures, and conflicts between traditional customs and individual desires. In Islamic law, marriage must fulfill essential pillars, including the presence of a legitimate guardian (wali) and witnesses; silariang often bypasses these requirements, rendering the marriage invalid from a religious perspective. Social consequences include severe sanctions for the perpetrators and enduring stigma within families. Modernization creates tensions between upholding adat values and respecting personal freedoms. This study utilizes an empirical legal approach with qualitative descriptive methods based on literature review and participatory observation. The research aims to analyze silariang through Islamic law and propose just and culturally sensitive solutions for the Bugis people.